Discourse on AI vs. Human Interaction among Generation Z: Trends, Challenges, and Future Directions - Bista, Shradhda (BIC Journal of Management, 2025)
The drastic change in the acceptance and incorporation of artificial intelligence (AI) into social communication has been profoundly changed in Generation Z (Gen Z) interacts, builds, and maintains relationships and views human connection. This paper examines the shifting conversation about digital newborns from 1997 to 2012, specifically the debate over human interaction versus AI interaction, through a thorough literature review of more than 60 peer-reviewed sources. The finding shows that even though Gen Z is very adept at using AI-mediated communication using chatbots, recommendation algorithms, and AI-powered social media platforms with ease, reliance raises questions about social isolation, cognitive dependency, and the disappearance of traditional interpersonal skills. Recent trend shows that Gen Z uses AI for more efficiency, management of emotion, and personalised experiences, discovering it as a collaborative partner rather than software or a tool. Even so, problems like reduced in-person communication, algorithmic anxiety, and a loss of authenticity still draw attention to possible threats to emotional intelligence and critical thinking. To better understand this dynamic, the study proposes a conceptual framework that integrates the Human-AI Integration Theory, Digital Nativity Theory, and Technology Acceptance Model (TAM). According to the study, incorporating AI in a way that enhances communication while still preserving crucial human interaction is necessary. Ethical AI designs, Digital literacy programs, and additional ongoing research to evaluate long-term social and cognitive effects are among the recommendations. Developing an equilibrium relationship between technology and human connection will be essential for the prosperity of society as Gen Z takes on leadership roles in an increasingly AI-driven world.